The role of knowledge management processes in strategic planning - an exploratory study of the opinions of a sample of college council members at the University of Karbala - حيدر محمد الجشعمي,; حسين حريجة غالي, (Iraqi Journal for Administrative Sciences, 2025)
The Study Aims to Determined Relationship and Impact Processes of Knowledge Management ( Creation , Store and Recupation , Transfer , Application ) in Strategic Planning for Opinions Sample from Members the Colleges Councils in Karbala University , in Order to Achieve the Aims of the Study , it is Divided to (5) Axis's , the First of Parade for the Study Methodology and Previous Studies, The Second Contains Theoretical Review for Study Variables, As for the Third to Touch on Description and Diagnosis Study Variables , The Forth of Parade the Hypothesizes Test and it Results Analysis , While the Fifth Refers to Conclusions and Recommendations, in Clued of the Study Sampling (30) Instructional from Members the Colleges Councils , Results Refer of Statistics Analysis to Be Sure of Hypothesis Rightness Absence , The Study Arrive at Several from Recommendations to Stress Necessity Prepare all Requirements Processes of Knowledge Management Because Main Channel to Increase Effectiveness and Efficiency of Strategic Planning